Deadly politics [large type] - Sefton, Maggie (A Molly Malone mystery, 2012)
Driven from Washington, D.C. by political back-stabbing, scandals, and personal heartbreak, Maggie Malone is now starting a new life in the place she swore she'd never come back to. Molly's politico niece, Karen, has set her up with a position in the office of a freshman senator. As the former wife of a congressman, Molly is alarmed to hear that Karen is having an affair with her boss. Just days later, she finds Karen shot to death. Discovering that Karen's boss ransacked her apartment, Molly investigates further . . .